Enhancement of thermal transport properties of asymmetric Graphene/hBN nanoribbon heterojunctions by substrate engineering - Medrano Sandonas L. (2017)
L.M.S. thanks to the International Max Planck Research School Dynamical processes in atoms, molecules and solids and the Deutscher Akademischer Austauschdienst(DAAD) for the financial support. G.C.S. and C.V.L. are grateful to National Council of Science and Technology (CONCYTEC) from Peru for the financial support through the Doctoral Program for Peruvian Universities (Nº 218-2014-CONCYTEC) and the Peruvian Excellence Center Program, respectively. This work has also been partly supported by the German Research Foundation(DFG) within the Cluster of Excellence “Center for Advancing Electronics Dresden”. We acknowledge the Center for Information Services and High Performance Computing (ZIH) at TU Dresden for computational resources.